Oculus imaginaries: The promises and perils of Facebook's virtual reality. (January 2022) - Egliston, Ben; Carter, Marcus
This article explores the Oculus suite of virtual reality (VR) technologies, with a specific focus on the period following the company's 2014 acquisition by Facebook. Through a close reading of promotional material, we first describe and analyse the 'Oculus imaginary' – the narrative produced by Facebook about the Oculus as integrated into and enhancing the experience of Facebook's wider suite of social software. The purpose of this narrative, we suggest, is to construct and 'sell' a Facebook-specific vision of VR's potentials – one that is appealing both to end users and platform complementors – and moreover, a vision that appears to be conducive to Facebook's current methods for accumulating profit and power. Following on, we develop via a study of YouTube user comments posted on promotional videos for the Oculus, an anticipatory account of how the Oculus imaginary is perceived to relate to the lives and values of everyday individuals.